Ratchet effects revisited: power effects and systematic bias in natural resource management - Jordan S. Rosenfeld (FACETS)
Regulatory ratchets arise when governance appears to be effective, but actually masks a steady loss of natural capital. This occurs when biases in environmental impact assessment (EIA) systematically underestimate the true impact of large developments, generated by statistical convention fixing α at 0.05 (Type 1 error or false positive rate; i.e., the probability of concluding that a development will have an impact when there is none) while β, the false negative rate (failing to detect a true impact, or Type 2 error), is often fixed at 0.2. This asymmetry (β > α) generates a higher likelihood of mistakenly permitting development than mistakenly preventing it. Beyond statistical bias in EIA, routine environmental regulations are often ineffective due to low compliance, inadequate thresholds, and broad exemptions, which tend to cryptically institutionalize net loss. Measuring bias and inefficiency of environmental regulation is foundational to correcting regulatory ratchets and identifying pathways towards no net loss. Like net loss from major developments, cumulative net loss from inadequate routine environmental protections also needs to be estimated and offset by active habitat restoration; this should be delivered as a core program of resource management agencies, with the goal of fully integrating the mitigation hierarchy into routine natural resource governance.